De novo development of dural arteriovenous fistula after endovascular embolization of pial arteriovenous fistula. (17th April 2012) - Paramasivam, Srinivasan; Toma, Naoki; Niimi, Yasunari; Berenstein, Alejandro
Abstract : Background: The development of de novo dural arteriovenous fistula(s) following endovascular embolization of a prior high-flow pial arteriovenous fistula (PAVF) has not previously been reported and the natural history is unknown. The anatomic basis, pathophysiologic mechanism, management and outcome are discussed. Methods: Treatment-completed congenital PAVFs treated at our center between January 2005 and August 2011 were analyzed retrospectively. Among 16 cases of PAVFs treated by endovascular embolization, four developed de novo dural arteriovenous fistulas during treatment or on follow-up that were not present before treatment. Information was collected from the clinical case records, imaging by MRI on presentation and during follow-up, all angiographic images and records during each of the procedures and during follow-up. Results: The time interval between the last embolization and identification of a dural fistula ranged from 3 to 14 months. Ten fistulas were identified in four patients, seven of which were embolized, four with glue, two with Onyx18 and one with absolute alcohol. None recanalized, while one patient developed fistula in an adjacent location that was subsequently treated with radiosurgery. Not all fistulas need treatment; small fistulas with a minimal flow can safely be observed. Conclusions: De novo dural fistulas following endovascular embolization of high-flow PAVFs is not an uncommon development. They are mostly asymptomatic and develop anywhere along the drainage of the fistula, maturing over time and diagnosed during follow-up studies, emphasizing the need for follow-up angiography. They can be effectively treated by endovascular embolization. Localized refractory dural fistulas can be dealt with by radiosurgery.